EFFECTIVENESS OF FISH FEED FORMULATION WITH CHICKEN FEATHER MEAL BASED ON SNI STANDARDS FOR NILE TILAPIA - Fitriana, Wiwit Denny; Novitasari, Afsah; Qomariana, Anna; Anugrah, Chandra Sukma; Islami, Mohamad Fajril (Jurnal Perikanan Unram, 2025)
This study aims to evaluate the effectiveness of Nile Tilapia feed formulation using feather meal as one of the primary ingredients, based on the Indonesian National Standard (SNI). Laboratory tests were conducted to measure the chemical composition of the feed, including ash content, moisture content, fat content, protein content, crude fiber, as well as contaminants such as heavy metals, antibiotic residues, and Salmonella. The results showed that the feed had a protein content of 32.31% and a fat content of 9.13%, both exceeding the minimum standards set by SNI. The ash, moisture, and crude fiber contents were also within safe limits. Additionally, the feed was free from Salmonella and antibiotic residues. However, heavy metals like cadmium (1.5 mg/kg) and mercury (1.69 mg/kg) exceeded the maximum limits recommended by SNI. Overall, the feed has good potential for use in Nile Tilapia farming but requires further control over heavy metal content.